Angiopoietin-like protein 2 induced by mechanical stress accelerates degeneration and hypertrophy of the ligamentum flavum in lumbar spinal canal stenosis. - Takayuki Nakamura (PLoS ONE, 2014)
Chronic inflammation and subsequent fibrosis induced by mechanical stress play an important role in ligamentum flavum (LF) hypertrophy and degeneration in patients with lumbar spinal canal stenosis (LSCS). Angiopoietin-like protein 2 (Angptl2) is a chronic inflammatory mediator induced under various pathological conditions and increases the expression of TGF-β1, which is a well-characterized mediator in LF hypertrophy. We investigated whether Angptl2 is induced by mechanical stress, and whether it contributes to LF hypertrophy and degeneration by activating the TGF-β1 signaling cascade. In this study, we investigated human LF tissue and LF fibroblasts isolated from patients who underwent lumbar surgery. We found that Angptl2 was abundantly expressed in fibroblasts of hypertrophied LF tissues at both the mRNA and protein levels. This expression was not only positively correlated with LF thickness and degeneration but also positively correlated with lumbar segmental motion. Our in vitro experiments with fibroblasts from hypertrophied LF tissue revealed that mechanical stretching stress increases the expression and secretion of Angptl2 via activation of calcineurin/NFAT pathways. In hypertrophied LF tissue, expression of TGF-β1 mRNA was also increased and TGF-β1/Smad signaling was activated. Angptl2 expression in LF tissue was positively correlated with the expression of TGF-β1 mRNA, suggesting cooperation between Angptl2 and TGF-β1 in the pathogenesis of LF hypertrophy. In vitro experiments revealed that Angptl2 increased levels of TGF-β1 and its receptors, and also activated TGF-β1/Smad signaling. Mechanical stretching stress increased TGF-β1 mRNA expression, which was partially attenuated by treatment with a calcineurin/NFAT inhibitor or Angptl2 siRNA, indicating that induction of TGF-β1 expression by mechanical stretching stress is partially mediated by Angptl2. We conclude that expression of Angptl2 induced by mechanical stress in LF fibroblasts promotes LF tissue degeneration by activation of TGF-β1/Smad signaling, which results in LF hypertrophy in patients with LSCS.